An overview of animal brucellosis in the province of El-Oued (Algerian Sahara) - Khezzani, Bachir; Aouachria, Amira Nrimane; Djaballah, Sonia; Djedidi, Teber; Bosilkovski, Mile (Journal of Fundamental and Applied Sciences, 2020)
The main objective of this paper is to give an overview of animal brucellosis situation inEl-Oued province by analyzing a series of statistical data. The results show that 37.9% of theteste danimalshad a positive result. The highest seroprevalence was noted in goats with 38.2%,further more, the high incidence rate has been reported in cattle with 35.9 per 100,000 animals.Females are more exposed to brucellsis than males by 99%, the annual distribution of theincidence characterized by a strong fluctuation with an upward trend. In addition, the highestincidence rate was reported in the spring at 2.74 per 100,000 animals. Although local healthauthorities are making enormous efforts to limit brucellosis, the epidemic is still widespreadin the study area. This situation requires a series of urgent and specific preventive andtherapeutic measures.